Carbapenem-resistant K. pneumoniae exhibiting clinically undetected amikacin and meropenem heteroresistance leads to treatment failure in a murine model of infection. (November 2021) - Zhang, Feiyang; Ding, Manlin; Yan, Xiangjin; Bai, Jiawei; Li, Qin; Zhang, Biying; Liang, Qinghua; Liang, Shuang; Wang, Guangxi; Zhou, Yingshun
Abstract: Heteroresistance is a poorly understood mechanism of resistance which refers to a phenomenon where there are different subpopulations of seemingly isogenic bacteria which exhibit a range of susceptibilities to a particular antibiotic. In the current study, we identified a multidrug-resistant, carbapenemase-positive K. pneumoniae strain SWMUF35 which was classified as susceptible to amikacin and resistant to meropenem by clinical diagnostics yet harbored different subpopulations of phenotypically resistant cells, and has the ability to form biofilm. Population analysis profile (PAP) indicated that SWMUF35 showed heteroresistance towards amikacin and meropenem which was considered as co-heteroresistant K. pneumoniae strain. In vitro experiments such as dual PAP, dual Times-killing assays and checkerboard assay showed that antibiotic combination therapy (amikacin combined with meropenem) can effectively combat SWMUF35. Importantly, using an in vivo mouse model of peritonitis, we found that amikacin or meropenem monotherapy was unable to rescue mice infected with SWMUF35. Antibiotic combination therapy could be a rational strategy to use clinically approved antibiotics when monotherapy would fail. Furthermore, our data warn that antibiotic susceptibility testing results may be unreliable due to undetected heteroresistance which can lead to treatment failure and the detection of this phenotype is a prerequisite for a proper choice of antibiotic to support a successful treatment outcome. Highlights: Carbapenem-resistant K . pneumoniae has become a cause of nosocomial infections and posed challenges on treatments. Heteroresistance could lead to treatment failure and is difficult to detect by methods employed by clinical laboratories. Amikacin is often combined with carbapenems against multi-drug resistant K . pneumoniae . Reports of amikacin and meropenem heteroresistant K. pneumoniae in China has not been previously reported.